Cover Picture: Metal–Phenolic Carbon Nanocomposites for Robust and Flexible Energy‐Storage Devices (ChemSusChem 8/2017). Issue 8 (11th April 2017) - Oh, Jun Young; Jung, Yeonsu; Cho, Young Shik; Choi, Jaeyoo; Youk, Ji Ho; Fechler, Nina; Yang, Seung Jae; Park, Chong Rae
Abstract : The Cover picture shows a metal–